2009
DOI: 10.1103/physrevlett.103.065502
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Stabilized Surface Reconstructions at Polar ZnO(0001)

Abstract: The atomic structure of the polar ZnO(0001) surfaces in a dry and humid oxygen environment is studied combining diffraction experiments and density-functional theory. Our results indicate that for similar stoichiometries a large number of very different, but energetically almost degenerate reconstructions exist. Thus vibrational entropy, which could be safely neglected for most semiconductor surfaces becomes dominant, giving rise to a hitherto not reported strong dependence of surface phase diagrams on tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 25 publications
7
143
1
Order By: Relevance
“…The choices of low energy reconstructions without H follow previous investigations [53,57,69,70]. Specifically, on ZnO polar surfaces, although several different surface reconstruction models are proposed by both theoretical calculations and experiments [53,70], the surface energy differences among them are in the order of a few meV/Å 2 [70], suggesting that the (2×2) adatom reconstruction is adequate for our discussions here. For GaN, (2×2) adatom reconstructions were taken into consideration under the condition of N-rich [57].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The choices of low energy reconstructions without H follow previous investigations [53,57,69,70]. Specifically, on ZnO polar surfaces, although several different surface reconstruction models are proposed by both theoretical calculations and experiments [53,70], the surface energy differences among them are in the order of a few meV/Å 2 [70], suggesting that the (2×2) adatom reconstruction is adequate for our discussions here. For GaN, (2×2) adatom reconstructions were taken into consideration under the condition of N-rich [57].…”
Section: Methodsmentioning
confidence: 99%
“…However, the lowest energy configurations must be those surfaces that satisfy ECR [52,56]. It demonstrated that the vibrational entropy of the surface plays a decisive role in the competition among various phases to achieve thermodynamic stability [53]. And when the temperature (and pressure) effects of the gas phase reservoirs, which arises from vibrational contributions to the entropy [56], are significant in high temperature growth, it would constrain the reconstructions within a limited number of configurations with less hydrogen atoms [56].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations